Philippine Household Income Mobility Measurement and its Decomposition using a Pseudo-Longitudinal Panel Data - Monsura, Melcah Pascua (Journal of Reviews on Global Economics, 2020)
When economic growth does not translate into poverty reduction and it remains a challenge, it is crucial to examine income mobility since income is a measure of individual economic status or poverty status. To understand the role of economic growth on welfare when there is income mobility, this study measured the Philippine households’ income mobility utilizing pseudo-longitudinal panel data from the Family Income and Expenditures Survey (FIES) of 2003 to 2012. Using various income mobility indices such as chi-square, average jump index and Shorrocks mobility index, the results revealed that the households’ income movement was more mobile than expected. This means that the households’ income status improved through time, low-income rank moved to higher-income rank in a given income distribution. In addition, short-run income inequality was reduced by 87.30 percent (87.30%) when there was income mobility. The presence of income mobility in the country was mainly due to the transfer effect which indicates that households did not take the economic opportunities of economic growth to increase their economic status.